Condictivity anisotropy and pseudogap state evolution in HoBa₂Cu₃O₇₋δ single crystals of a present flat defect topology at decreasing oxygen concentration - Obolenskii, M.A.; Vovk, R.V.; Bondarenko, A.V.; Goulatis, I.L. (Functional Materials, 2006)
The temperature dependences of electrical resistance along the c-axis and in the abplane for HoBa₂Cu₃O₇₋δ single crystals with various oxygen content have been measured. The temperature dependences of the pseudogap value have been determined. These dependences have been shown to be described satisfactority within the frame of crossover (BSC-BEK) theory. The intensification of localization effects results in depression of the pseudogap state. A considerable anisotropy of the superconductive properties has been observed when measuring the temperature dependences of electrical resistance along and across the basis plane.